MicroRNA biogenesis - Kim, Narry (Henry Stewart Talks, 2007)
Definition of microRNA, Comparison to small interfering RNA, Mechanism of gene silencing, Factors in the microRNA pathway, RNase III proteins and their interacting proteins, MicroRNA gene structure and transcription, Drosha and primary microRNA processing, Exportin 5 and pre-microRNA export, Dicer and pre-microRNA processing, RISC assembly and strand selection, MicroRNA biogenesis in plants, Experimental tools to investigate microRNA
Reviewed at 2016/10/13